Investigation of Simultaneous Photons and Electrons Beam by Monte Carlo Code - Sardari, Dariush; Khaledi, Navid; Arbabi, Azim; Mohammadi, Mohammad; Ameri, Ahmad (Reports of Radiotherapy and Oncology, 2015)
Background: Depending on the location and depth of tumor, the electron or photon beams might be used for treatment. Electron beam have some advantages over photon beam for treatment of shallow tumors to spare the normal tissues beyond of the tumor. In the other hand, the photon beam are used for deep targets treatment. Both of these beams have some limitations, for example, the dependency of penumbra with depth, and the lack of lateral equilibrium for small electron beam fields. Objectives: In this study, improvement of the penumbra and Dmax changes will be investigated. Also the effects of cut-outs on the beam parameters prepared as well. Patients and Methods: In first, we simulated the conventional head configuration of Varian 2300 for 16 MeV electron, and the results approved by benchmarking the percent depth dose (PDD) and profile of the simulation and measurement. In the next step, a perforated Lead (Pb) sheet with 1 mm thickness placed at the top of the applicator holder tray. This layer producing bremsstrahlung x-ray and a part of the electrons passing through the holes, in result, we have a simultaneous mixed electron and photon beam. For making the irradiation field uniform, a layer of steel placed after the Pb layer. The simulation was performed for 10 × 10, and 4 × 4 cm2 field size. Results: The measured R50 and RP for 10 × 10 cm2 field were 6.5 and 7.8 cm, respectively. The photon percentage for 1 mm thickness with 0.2, 0.3, and 0.5 cm holes diameter Lead layer target was about 33%, 32%, and 28% and for 2 mm targets punched with 0.2, 0.3, and 0.5 cm holes, the x-ray percentages were 43%, 41%, and 35%. Conclusions: This study showed the advantages of mixing the electron and photon beam by reduction of pure electron’s penumbra dependency with the depth, especially for small fields, also decreasing of dramatic changes of PDD curve with irradiation field size.